2019
DOI: 10.1186/s12870-019-2093-3
|View full text |Cite
|
Sign up to set email alerts
|

Mining and genomic characterization of resistance to tan spot, Stagonospora nodorum blotch (SNB), and Fusarium head blight in Watkins core collection of wheat landraces

Abstract: Background: In the late 1920s, A. E. Watkins collected about 7000 landrace cultivars (LCs) of bread wheat (Triticum aestivum L.) from 32 different countries around the world. Among which 826 LCs remain viable and could be a valuable source of superior/favorable alleles to enhance disease resistance in wheat. In the present study, a core set of 121 LCs, which captures the majority of the genetic diversity of Watkins collection, was evaluated for identifying novel sources of resistance against tan spot, Stagonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 106 publications
(139 reference statements)
5
18
2
Order By: Relevance
“…Nevertheless, 25 lines (13%) resistant to both races (Race 1 and Race 5) have been identified in the present study. Regarding toxin sensitivities of the genotypes, a low but positive correlation was observed between Ptr ToxA sensitivity of the genotypes and disease susceptibility in the field, which is in contrast with the observations made by Friesen et al (2003) ; Faris and Friesen (2005) , Noriel et al (2011) , and Halder et al (2019) . We did not obtain any significant correlations between days to heading and plant height with Ptr resistance in field, suggesting that none of these phenological traits significantly affected tan spot resistance in the germplasm investigated.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, 25 lines (13%) resistant to both races (Race 1 and Race 5) have been identified in the present study. Regarding toxin sensitivities of the genotypes, a low but positive correlation was observed between Ptr ToxA sensitivity of the genotypes and disease susceptibility in the field, which is in contrast with the observations made by Friesen et al (2003) ; Faris and Friesen (2005) , Noriel et al (2011) , and Halder et al (2019) . We did not obtain any significant correlations between days to heading and plant height with Ptr resistance in field, suggesting that none of these phenological traits significantly affected tan spot resistance in the germplasm investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…Most wheat entries evaluated in the study showed a susceptible response to Race 1 (72.6%), whereas for Race 5, 67.5% of lines were resistant. It is a common observation in most germplasm collections ( Liu et al, 2015 ; Halder et al, 2019 ), and our results reinforce that finding resistance against Ptr Race 1 is very challenging compared to other races. Race 1 is the most prevalent worldwide ( Ali and Francl, 2003 ; Abdullah et al, 2017 ) and is reported to contain the virulence of Races 2 and 3, making it more aggressive than other races ( Lamari et al, 2003 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding MTA identified for AUDPC scores, most associations except the one on chromosome 3AL were identified within 2-3 Mb genomic region of the markers associated with seedling resistance to Races 1 and 5 or insensitivities to toxins Ptr ToxA and Ptr ToxB in the present study, thus confirming to be major genes (tsn 1, tsc2). Three associations on chromosomes 2BS, 4AL, and 6BS overlap with minor QTL reported for tan spot resistance in previous studies (Gurung et al, 2011;Halder et al, 2019). The QTL found on chromosome 3AL is likely new for adult plant resistance, which was identified only at adult plant stage in the present study.…”
Section: Discussionsupporting
confidence: 78%